Gait analysis using the Oxford Foot Model for ankle arthrodesis compared with normal control. Issue 3 (14th September 2018) - Ota, Yuki; Nakasa, Tomoyuki; Sawa, Mikiya; Yoshikawa, Masahiro; Tsuyuguchi, Yusuke; Kanemitsu, Munekazu; Adachi, Nobuo
Category: Ankle Arthritis Introduction/Purpose: Ankle arthrodesis is still the primary treatment for end-stage arthritis of the ankle that does not respond to conservative treatment. However, comparative studies demonstrated that the patients' functional outcomes remain significantly lower than normal, progression of subtalar and midfoot arthritis and there could be measurable abnormalities in their gait parameters. Previous studies demonstrated gait analysis after ankle arthrodesis using 3D motion capture system. These studies used a single segment foot model, which had the limitation of detailed motion analysis. 3D multi-segmental foot model enables to perform detailed analysis segmentally such as fore foot and hind foot. The purpose of this study was to examine foot kinematics during walking after ankle arthrodesis using 3D multi-segment foot model as compared with a healthy control group. Methods: Between 2014 and 2016, nine patients who underwent an isolated ankle arthrodesis were followed for a mean 2 years after surgery, and five control subjects were included for comparison. Physical examination, radiographic examination and gait examination were performed. For gait analysis Vicon Nexus system with 16 MX-Cameras was used to capture foot kinematics during barefoot walking at self-selected speed along a 10 m walkway. Markers were placed according to the Oxford Foot Model (OFM). Patients completed preoperative and annual postoperative functional outcome scores including the Japanese Society for Surgery of the Foot (JSSF) scale. Results: JSSF scale was significantly improved from pre-operation to post-operation (50 points versus 85 points; p<0.05). The range of sagittal motion in hind foot during one gait cycle was significantly smaller in the arthrodesis group than in the healthy group (4.6 degrees versus 20 degrees; p<0.05). The range of coronal motion in hind foot was also significantly smaller in the arthrodesis group than that in the healthy group (3.7 degrees versus 15.1 degrees; p<0.05). There was no significant difference in the range of sagittal motion in forefoot between arthrodesis group and healthy group (20.2 degrees versus 16.6 degrees). However, there were significant differences at heel contact. Forefoot in arthrodesis group was significantly toward plantarflexion (6.1 degrees versus -2.0 degrees; p<0.05). Conclusion: In this study, detailed motion of foot after ankle arthrodesis could be analyzed by using OFM. Range of sagittal motion in hind foot in arthrodesis group during one gait cycle was significantly smaller than that in healthy group. However, no significant difference was observed in the forefoot. The same result was also obtained on the frontal plane. In arthrodesis group, forefoot tended to be more plantarflexion than healthy group in gait, especially there was significant difference at heel contact. These findings suggested to cause lower functional outcomes and the progression of subtalar and midfoot arthritis after ankle arthrodesis.